2018
DOI: 10.1101/399253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene co-expression is distance-dependent in breast cancer

Abstract: Breast carcinomas are characterized by anomalous gene regulatory programs. As is well known, gene expression programs are able to shape phenotypes. Hence, the understanding of gene co-expression may shed light on the underlying mechanisms behind the transcriptional regulatory programs affecting tumor development and evolution. For instance, in breast cancer, there is a clear loss of inter-chromosomal (trans-) co-expression, compared with healthy tissue. At the same time cis-(intrachromosomal) interactions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 66 publications
4
9
0
Order By: Relevance
“…In previous works from our group, we observed abrupt changes in the way that genes co-express: for instance, we have documented a substantial decrease of inter-chromosome ( trans- ) gene-gene interactions in breast cancer (Espinal-Enriquez et al, 2017 ; Dorantes-Gilardi et al, 2020 ; García-Cortés et al, 2020 ). We decided to separate gene-gene interactions into intra-chromosome ( cis- ) and inter-chromosome ( trans- ).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…In previous works from our group, we observed abrupt changes in the way that genes co-express: for instance, we have documented a substantial decrease of inter-chromosome ( trans- ) gene-gene interactions in breast cancer (Espinal-Enriquez et al, 2017 ; Dorantes-Gilardi et al, 2020 ; García-Cortés et al, 2020 ). We decided to separate gene-gene interactions into intra-chromosome ( cis- ) and inter-chromosome ( trans- ).…”
Section: Introductionmentioning
confidence: 72%
“…(1) pre-normalization quality control, (2) batch and bias corrections (normalization) and (3) post-normalization quality control. Data pre-processing was conducted as previously (Drago-García et al, 2017 ; Espinal-Enriquez et al, 2017 ; de Anda-Jáuregui et al, 2019b , c ; García-Cortés et al, 2020 ; Serrano-Carbajal et al, 2020 ). Briefly, we assessed (a) biotype abundances, to assure that samples contained protein coding genes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously [6][7][8], we observed that in breast cancer, trans-(inter-chromosome) gene interactions are more scarce and weaker in cancer samples compared to the healthy phenotype. Furthermore, in breast cancer, cis-interactions become stronger, however, this is strongest between physically close genes, and this gene correlation strength decays with the distance.…”
Section: Spatial Anomalies In Cancer-associated Grpsmentioning
confidence: 80%
“…, we identify that interchromosomal interactions between genes in any pair of chromosomes have more losses than gains of MI in disease, with an average MI loss greater than the average MI gain. Meanwhile, intrachromosomal interactions may exhibit three different behaviors: (i) they have more losses with higher average MI loss, although with higher GLS and GLR values than the interchromosomal interactions (chromosomes 1, 2, 5, 6, 11, 17, 19, X); (ii) they have more losses, but the average MI gain is higher (chromosomes 3,4,7,8,9,10,12,13,14,15,16,18,19,20,22) or (iii) they have more gains, with a higher average MI gain (21).…”
Section: Intra-and Inter-chromosome Interactions Exhibit Differences mentioning
confidence: 99%